Rumeksa ing Wengi: Nyanyian Pemanggil Kuntilanak atau Kidung Religius - Perdana Setya Prasanto (SHAHIH: Journal of Islamicate Multidisciplinary, 2019)
In the modernization era, shift-meaning phenomenon often appears in our society, for instance, shifted the meaning of Islamic cultural heritage in Kidung Rumeksa ing Wengi from Sunan Kalijaga. Kuntilanak trilogy movies 2006-2008 influenced the new perception of society about Kidung Rumeksa ing Wengi. Before, it was a medium of Sunan Kalijaga delivering Islamic message. But, the Kidung representation has shifted as a spirit caller song. In 2019, horror movie reproduced Lingsir song within Kidung Rumeksa ing Wengi. This shift-meaning among the society has trigerred misunderstanding of the kidung. So, this research employs a literature approach will examine Kidung Rumeksa ing Wengi in religious perspective. The religious meaning of the Kidung provides aqeedah and morality, and those are considered as society belief that Kidung Rumeksa ing Wengi is not spirit caller song.